PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KONTRAK POILA II PADA PT. ASURANSI BRI LIFE JAKARTA - Istiqomah (Al Hasanah Barokah Foundation, 2024)
The aim of this research is to find out whether compensation and work discipline influence the performance of pattern II contract employees at PT. BRI Life Insurance Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 72 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. There is a positive and significant influence between compensation on the performance of pattern II contract employees at PT. BRI Life Insurance with a value of tcount (2.196) > ttable (1.995) and sig (0.031) < 0.05. There is a positive and significant influence between work discipline on the performance of pattern II contract employees at PT. BRI Life Insurance with a value of tcount (6.669) > ttable (1.995) and sig (0.000) < 0.05. There is a positive and significant influence between compensation and work discipline together on the performance of pattern II contract employees at PT. BRI Life Insurance with a value of Fcount (147.886) > Ftable (3.13) and sig (0.000) < 0.05, the level of relationship between compensation and work discipline on the performance of pattern II contract employees at PT. BRI Life Insurance is said to be very strong with a correlation coefficient (R) of 0.900.